2021
DOI: 10.3389/frsus.2021.790807
|View full text |Cite
|
Sign up to set email alerts
|

Flying High in Academia—Willingness of University Staff to Perform Low-Carbon Behavior Change in Business Travel

Abstract: This study aims to explore the factors that influence business travel decisions of university staff, in particular the extent and ways in which they are willing to reduce emission-intensive air travel, and the personal and structural barriers to such behavior change. Three strategies to reduce air travel were investigated: abstaining from particular events, substituting travel through virtual participation and mode shifting to ground-based public transport. We tested the effects of (1) specific decision factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In our case, for example, distinguished senior researchers that choose to fly less, may serve as role models for others and build broader support for measures to reduce academic flying. A key point, in line with our understanding of frequent flying in academia as a case of carbon lock-in, is that systemic change is necessary to enable individuals in academia to fly less (Whitmarsh et al , 2020; Nursey-Bray et al , 2019; Thaller et al , 2021b). Yet, this systemic change may be pushed forward by the embedded agency of committed and resourceful individuals (Garud et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, for example, distinguished senior researchers that choose to fly less, may serve as role models for others and build broader support for measures to reduce academic flying. A key point, in line with our understanding of frequent flying in academia as a case of carbon lock-in, is that systemic change is necessary to enable individuals in academia to fly less (Whitmarsh et al , 2020; Nursey-Bray et al , 2019; Thaller et al , 2021b). Yet, this systemic change may be pushed forward by the embedded agency of committed and resourceful individuals (Garud et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we collected sociodemographic data, in particular concerning staff type (predoc researchers/postdoc researchers and lecturers/professors/administrative staff). Further questions on travel behaviour and travel decision factors were evaluated in a separate study (Thaller et al , 2021b). The survey was completed by 355 staff members, but we excluded those with an incorrect answer to the control question, leaving a final sample size of n = 338 (267 academic and 71 administrative staff, response rate 11.5%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously to the current study, a survey was conducted at the University of Graz that investigated the willingness to reduce flight travel (Thaller et al , 2021) and the support of reducing flight travel measures amongst the staff (Schreuer et al , 2023). Thaller et al (2021) found that the willingness to reduce future international air travel is generally high for a clear majority of scientists, depending also on previous experiences and the event type creating the purpose for travel. The willingness to reduce flight trips is found to be higher for shifting to a different travel mode than for shifting to online participation or abstaining from participation.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A first step to reduce travel GHG emissions could be to identify “unnecessary” trips (Pargman et al , 2022), especially those taken by the high emitting scientist groups, i.e. natural sciences and senior researchers, according to the results of this study, and hence avoid the necessity to fly (Creutzig et al , 2018) and the trips themselves (Thaller et al , 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%